Condom failure and pre-exposure prophylaxis use experience among female sex workers in Ethiopia: a qualitative study - Minilik Demissie Amogne; Eduard J. Sanders; Wudinesh Belete Belihu; Jesper Sundewall; Anette Agardh (BMC, 2022)
Abstract Background Female sex workers (FSW) remain a highly exposed group for HIV/STIs due to different factors including condom failure. In Ethiopia, pre-exposure prophylaxis (PrEP) has recently been introduced as an intervention strategy to prevent new HIV infections, but knowledge about FSWs' experiences of condom failure and PrEP use remains scarce. Therefore, this study explores FSWs' experiences concerning condom failure and their attitudes towards, and experiences of, PrEP uptake. Method A qualitative study using in-depth interviews was conducted among FSWs in Addis Ababa. A manifest and latent content analysis method was applied to identify categories and emerging themes. Result Seventeen FSWs (10 who started on PrEP, 1 who discontinued, and 6 who didn't start) were interviewed. FSWs described the reasons behind condom failure, the mechanisms they used to minimize the harm, and their attitudes towards PrEP use. FSWs struggled with the continuous risk of condom failure due to factors related to clients' and their own behavior. PrEP was mentioned as one the strategies FSWs used to minimize the harm resulting from condom failure, but PrEP use was compounded with doubts that deterred FSWs from uptake. FSWs' misconceptions, their lack of confidence, and PrEP side effects were also mentioned as the main challenges to start taking PrEP and/or to maintain good adherence. Conclusion The demands and behavior of the clients and FSWs' own actions and poor awareness were factors that increased the exposure of FSWs to condom failure. In addition, the challenges associated with PrEP uptake suggest the need for user-friendly strategies to counteract these barriers and facilitate PrEP uptake.